(untitled) (Global Scientific Review, 2023)
This article highlights the ways of creative approaches to solving problems in elementary school. The article defines the essence of cognitive interest, gives the characteristics of the main stages of its development, shows its relationship with the educational objectives of teaching mathematics, describes the ways and means of cognitive interest development.